SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN RUMPUT TERBAIK UNTUK TAMAN MENGGUNAKAN METODE AHP BERBASIS ANDROID - Maulina Wati; Yuswardi Yuswardi; Maryanti Maryanti; Zikrul Khalid (Jurnal Sains Riset, 2023)
Grass is one of the most commonlyused types of ground cover plants, especially for gardens. Because grass is the besttype of plant and has several funcitions.Besides being able to absorb water as well to reduce dustfrom the ground which is blown by the wind, besides that covering the gronud which is blown by the wind, besides that coverinbg the ground with grass will also make the garden look more exotic. Decision support systems(DSS)are part of a computer based information system icluding knowledge –based systemor knowledge management that are used to support decision making withun an organization or company.it can also be said as a computerb data into information to make decision on specific semi –structured problems. The abilility of the selection of the  best grass for gardering. Decision support system assistance can be felt more quickly and accurately if the decision support system is in the form of a computer. The ability of computer to process data to produce information is beyond doubt. The AHP method haas the advantage that there are paiwise comparisons for each criterion, so that each criterion . Based on these advantages , the AHP method is suintable and appropriate to use. Computer as a tool can process data based on software that is entered into the computer, to produce alternative decisionsi in choosing the best grass for gardening.Keywords : SPK, Selection of Grass, AHP Method. Park. Androids